Characterization of growth and visual symptoms of nitrogen, potassium and magnesium deficiencies in arugula - Silva, Paulo Henrique Soares; Reis, Isaias dos Santos; Nascimento, Camila Seno; Nascimento, Carolina Seno; Filho, Arthur Bernardes Cecílio (Emirates Journal of Food and Agriculture, 2021)
Arugula is a short-cycle species with a high demand for nutrients. In the plant, each nutrient performs one or more specific functions, so its deficiency will negatively impact the crop growth and development, being important to recognize the nutritional symptoms to help in decision making. In this context, the objective of this study was to describe the evolution of N, K, and Mg deficiencies symptoms and their effect on the growth of arugula plants. One at a time, the nutrients were omitted from the nutrient solution. At 13, 16, 18, and 20 days after transplanting (DAT) the seedlings to the - Nutrient Film Technique (NFT) system, plants were collected, symptoms characterized, and leaves were scanned in JPEG (1.200 pixels). At 10 DAT of arugula, plants grew in a nutrient solution N-depleted shown the initial visual symptoms of N deficiency and at 16 DAT was recorded the first symptoms of K and Mg depletion in nutrient solution. At 20 DAT, the plants showed severe N deficiency symptoms, the old leaves presented intense and generalized chlorosis, followed by necrosis. Deficient plants in K exhibited chlorosis at the edge of old leaves advancing to the center of the leaves and small white dots. For Mg, the older leaves developed interveinal chlorosis from the leaf tip towards the central vein. The omission of nitrogen resulted in plants with lower height, leaf area, and number of leaves when compared to arugula plants grown in a complete nutrient solution.